2013
DOI: 10.1007/s00213-013-3181-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking on the acoustic startle response and prepulse inhibition in smokers with and without posttraumatic stress disorder

Abstract: Rationale Cigarette smokers smoke in part because nicotine helps regulate attention. Prepulse inhibition (PPI) of the startle reflex is a measure of early attentional gating that is reduced in abstinent smokers and in groups with attention regulation difficulties. Attention difficulties are found in people with posttraumatic stress disorder (PTSD). Objectives The aim of this study is to assess whether smoking and abstinence differentially affect the startle response and PPI in smokers with and without PTSD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 53 publications
1
27
2
Order By: Relevance
“…Other studies of ASR latency and magnitude in PTSD have not reached a consensus. While the association between PTSD and longer startle latency in our population contrasts with a study conducted by Vrana et al, which found faster latency in PTSD, that study did not consider the effects of TOXO (Vrana et al 2013). The literature on ASR magnitude in PTSD is also inconclusive.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies of ASR latency and magnitude in PTSD have not reached a consensus. While the association between PTSD and longer startle latency in our population contrasts with a study conducted by Vrana et al, which found faster latency in PTSD, that study did not consider the effects of TOXO (Vrana et al 2013). The literature on ASR magnitude in PTSD is also inconclusive.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, research shows that persons with PTSD show especially heightened anxiety in response to stressors and smoking appears to reduce such distress (Beckham et al, 2005, 2007). We believe that smoking may reduce heightened anxiety amongst persons with PTSD either directly (Hogle et al, 2010), or via its effects on attentional processing or by mitigating sensorimotor gating deficits (Baschnagel & Hawk, 2008; Calhoun et al, 2011; Vrana et al, 2013). Some research fails to show that smoking reduces acoustically elicited startle in smokers with PTSD, casting doubt on the notion that smoking exerts anxiolytic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Some research fails to show that smoking reduces acoustically elicited startle in smokers with PTSD, casting doubt on the notion that smoking exerts anxiolytic effects. However, those results may be challenged on the bases of the timing of the smoking experience in those studies and the fact that the startle paradigm may have primarily activated fear and not anxiety (Calhoun et al, 2011; Vrana et al, 2013), with the latter likely being more sensitive to smoking effects (Hogle et al, 2010; Jonkman et al, 2008). In short, we believe that smokers with PTSD are likely to show especially strong anxiety reactions to stressful stimuli, and that nicotine can quell such reactions (Beckman et al, 2005, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that one symptom cluster in PTSD, emotional numbing, a negative symptom similar to depression, is strongly associated with smoking frequency and difficulty quitting (Greenberg et al, 2012). Similarly, acoustic startle, which may reflect baseline arousal, isx enhanced in PTSD patients and by nicotine, but smoking cessation results in decreased startle (Vrana et al, 2013). Hyper arousal, another symptom cluster in PTSD, is shown to be reduced by nicotine (Beckham et al, 2007).…”
Section: Post-traumatic Stress Disorder and Drug Abusementioning
confidence: 99%